G40(P) MDT safety briefing in a paediatric intensive care unit: a 4 year evaluation of implementation and safety trends. (May 2019) - McGalliard, R; Cavanagh, S; Quinn, S; Keaney, A
Abstract : Aims: This study aimed to evaluate the implementation and long term outcomes of a daily safety briefing (SB) in a 12 bed paediatric Intensive Care Unit from January 2014 to December 2017. Potential safety issues and adverse outcomes were discussed. Methods: Data was extracted from contemporaneous recorded SB proforma and analysed by Microsoft Excel. Success of implementation and multidisciplinary involvement was examined through frequency, attendance at SB and staff surveys. Results: SB mean duration was 6.05 min (SD 0.672, range 2–20) and occurred on 29.7 days/month. Mean daily staff attendance was 7.77 (SD 0.82). Staff survey after SB implementation indicated an increasing agreement that there was a learning culture. Potential safety issues included prescribing, equipment, human factors and social concerns. Incident reporting increased from pre study levels due to increased reporting of near misses and mild/moderate harm events again supporting an increased safety awareness amongst staff (table 1 ). Annual trends in adverse incidents remained largely unchanged (table 2 ). Conclusions: The SB became an embedded and valued component of PICU that has resulted in greater awareness of potential safety issues and improved safety culture.